2015
DOI: 10.1590/0100-2945-117/14
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento De Genótipos De Abacaxizeiro Resistentes À Fusariose Em Comparação a Cultivares Comerciais Suscetíveis

Abstract: RESUMO -A fusariose é a doença mais severa na cultura do abacaxi no Brasil, e as cultivares mais plantadas, 'Pérola' e 'Smoth Cayenne', são suscetíveis, com perdas estimadas em 30 a 40% dos frutos. O uso de genótipos resistentes à doença abre grande perspectiva para a solução do problema. O objetivo deste trabalho foi avaliar, em experimento de campo, o potencial produtivo, as características das plantas e a qualidade de frutos de novos híbridos de abacaxi resistentes à fusariose: EC-105, EC-93, cv. BRS Vitóri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
3
10
0
6
Order By: Relevance
“…Vitória of 13.6 cm and 10.8 cm, respectively (BERILLI et al, 2014). Caetano et al (2015), when cultivating genotypes resistant to Fusarium planted on May 2006 and induced at 11 months after planting, observed fruit length and fruit diameter of 14.7 cm and 10.9 cm in 'Vitória' pineapple, respectively. The values reported by the authors are close to those found in the present study.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Vitória of 13.6 cm and 10.8 cm, respectively (BERILLI et al, 2014). Caetano et al (2015), when cultivating genotypes resistant to Fusarium planted on May 2006 and induced at 11 months after planting, observed fruit length and fruit diameter of 14.7 cm and 10.9 cm in 'Vitória' pineapple, respectively. The values reported by the authors are close to those found in the present study.…”
Section: Resultsmentioning
confidence: 97%
“…The best result of the diameter of the central cylinder for the different types of shootss was observed in fruits originated from sucker type (0.91 cm), corresponding to the lowest value in comparison to slips (0.99 cm). Caetano et al (2015), evaluating pineapple genotypes resistant to Fusarium in comparison to susceptible commercial cultivars, found in cv. Vitória, the lowest diameter of the central cylinder, 1.0 cm, a value close to those of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cultivars are susceptible to fusariosis, caused by the fungus Fusarium subglutinans, which is a highly destructive disease that can cause estimated losses of 30 to 40% of infructescences. In this sense, new cultivars resistant to fusariosis were introduced to replace the two most widespread cultivars in the country, such as the 'Imperial' (Cabral & Matos, 2005;Ventura et al, 2009;Caetano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This cultivar was obtained from the crossing of 'Perolera' with 'Smooth Cayenne', by Embrapa Mandioca and Fruticultura, resistant to fusariosis and internal darkening of the infructescence, which allows the reduction of the use of fungicide, with a reduction in the costs of production (Cabral & Matos, 2005). The plants are medium size, without spines at the edges, infructescence with high sugar content, moderate titratable acidity and moderate ascorbic acid content (Cabral & Matos, 2005;Caetano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%